2019
DOI: 10.1021/acs.cgd.9b00782
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Inorganic Solution Components on Lithium Carbonate Crystal Growth

Abstract: Lithium-bearing brines are an increasingly attractive source of Li for extraction. One extraction mechanism is the removal of Li from the fluid phase through the precipitation of zabuyelite (Li2CO3). The chemistry of the brine plays an important role in this process because ions in solution can compete for the components of the Li-carbonate phase. Here we explore the effect of different brine components on the precipitation of zabuyelite using experiments and computational simulations. Crystals formed in all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 80 publications
2
4
0
Order By: Relevance
“…From Figure , it can be seen that the Li 2 CO 3 precipitation rate considerably decreases in the presence of sulfate, in accordance with the reported delaying effect of sulfate ions on Li 2 CO 3 (s) nucleation . The delaying effect is reduced in high-ionic strength solutions, although no precipitation occurs within the experiments time; thus, no recovery and purity were calculated.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…From Figure , it can be seen that the Li 2 CO 3 precipitation rate considerably decreases in the presence of sulfate, in accordance with the reported delaying effect of sulfate ions on Li 2 CO 3 (s) nucleation . The delaying effect is reduced in high-ionic strength solutions, although no precipitation occurs within the experiments time; thus, no recovery and purity were calculated.…”
Section: Resultssupporting
confidence: 81%
“…In all cases, it must stress that, Ca 2+ , Sr 2+ , and Mg 2+ carbonate compounds have a low solubility that likely causes a CO 3 2− consumption. This is also confirmed by results presented by King et al 32 that detected traces of CaCO 3 and MgCO 3 in Li 2 CO 3 compounds precipitated from Li solutions containing 0.033 M Ca 2+ and Mg 2+ . The simultaneous presence of the three interfering cations (Ca 2+ , Sr 2+ , and Mg 2+ ) inhibits Li 2 CO 3 precipitation, most likely due As already commented in Figure 6, Li + recovery can reach a value around 70% for high-ionic strength solutions without any divalent ions.…”
Section: Influence Of Temperature and Ionic Strengthsupporting
confidence: 90%
See 1 more Smart Citation
“…[48] In particular, the Ca 2+ could compete with Li + for CO 3 2+ to form CaCO 3 , resulting in insufficient precipitation of Li 2 CO 3 . [49,50] Therefore, reducing the leaching of impurity ions is necessary for the precipitation of Li 2 CO 3 . [51,52] Calcium oxide was first added to remove Mg 2+ and SiO 3 2À :…”
Section: Concentration and Purification Of The Leachatementioning
confidence: 99%
“…[21] It is possible that the difference between the theoretical solubility data reported in the literature for Li 2 CO 3 and the experimental results found in this work can be explained by the different chemical composition of the aqueous solutions. King et al [22] found that the composition of the aqueous solution contributes either positively or negatively to the formation of Li 2 CO 3 and demonstrated, using experiments and computational simulations, that low concentrations of Na + ions have minimal influence on the precipitation of Li 2 CO 3 . However, if the Na + concentration is increased to 1 M, the time required for the precipitation of Li 2 CO 3 increases.…”
Section: Effect Of Ph On the LI 2 Co 3 Saturation-evaporation Stagementioning
confidence: 99%